2012
DOI: 10.3347/kjp.2012.50.4.309
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Maintenance of Clonorchis sinensis Adult Worms

Abstract: Clonorchis sinensis is a biological carcinogen inducing human cholangiocarcinoma, and clonorchiasis is one of the important endemic infectious diseases in East Asia. The present study investigated survival longevity of C. sinensis adult worms in various in vitro conditions to find the best way of keeping the worms longer. The worms were maintained in 0.85% NaCl, 1×PBS, 1×Locke's solution, RPMI-1640, DMEM, and IMDM media, and in 1×Locke's solution with different supplements. All of the worms died within 3 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The collected metacercariae were preserved in cold (4°C) 1× PBS with antibiotics until use. The metacercariae were introduced to male New Zealand white rabbits and adult C. sinensis worms were recovered as described in our previous study [3].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The collected metacercariae were preserved in cold (4°C) 1× PBS with antibiotics until use. The metacercariae were introduced to male New Zealand white rabbits and adult C. sinensis worms were recovered as described in our previous study [3].…”
Section: Methodsmentioning
confidence: 99%
“…The fresh worms were distributed in a 6-well culture plate by 10 worms per culture well with 3 mL of test solution or media as described in the previous study [3]. All of the experiment procedures were performed in triplicates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, bile acids trigger physiological stimuli; however, these metabolites can have detrimental effects on C. sinensis survival, as evidence suggests that the accumulated bile acids can cause toxicity to the worm's tissues and cells [18,19]. Recent studies reported that bile components can be toxic or detrimental to C. sinensis survival [10,20,21]. Under in vitro conditions, higher concentration (> 0.005%) of bile and lithocholic acid signi cantly decreased the worm survival [10,20,21].…”
Section: Introductionmentioning
confidence: 99%